Wise, strange, and holy : the strange woman and the making of the Bible - Camp, Claudia V., 1951- (Journal for the study of the Old Testament. Supplement series, 2000)
The relationship of the Strange Woman and Woman Wisdom, separate but inseparable in Proverbs 1-9, is the book's analytic starting point, becoming a hermeneutical lens for viewing other texts of strangeness-of gender, ethnicity, sexuality, and cultic activity. Wisdom and strangeness mark the narratives of Samson and Solomon, while priestly literature sets strangeness against holiness. Miriam and Dinah, sisters of cultic eponyms Aaron and Levi, are Israelite women defiled or unclean, made strange. Priestly and wisdom constructions of gendered strangeness intersect, illuminating the ideologies of.